The antecedents of tourist repeat visit intention: systemic approach. Issue 9 (13th July 2018) - Perovic, Ðurdica; Moric, Ilija; Pekovic, Sanja; Stanovcic, Tatjana; Roblek, Vasja; Pejic Bach, Mirjana
Abstract : Purpose: Contemporary tourism product, in terms of its systemic understanding, consists of tangible and intangible elements. These two elements lead to the increase of tourist satisfaction in a way to provide tourism products and services that match tourist expectations. Finally, tourist satisfaction is considered as a key factor influencing repeat visit intention. In line with mentioned, this study aims to empirically test a model linking tangible and intangible elements, tourist satisfaction and revisit intention. Design/methodology/approach: Using data from the Montenegrin survey called Guest Survey 2010, structural equations modelling has been used to determine the impact of tangible and intangible constructs on tourist satisfaction and tourist repeat visit intention in Montenegro. Findings: Working on a sample of 740 tourists, the results reveal that both tangible and intangible elements improve tourist satisfaction that influences tourist repeat visit intention. Noteworthy, the findings indicate that intangible elements have a stronger impact on tourist satisfaction than tangible elements have. Practical implications: Tangible and intangible elements as factors of satisfaction are analysed and evaluated so that they could be improved in a way that provides superior experience to tourists, which hopefully could result in repeat visitation that is considered as a tool for boosting destination competitiveness, thus indicating the need for the systemic approach to tourism management. Originality/value: This paper extends earlier tourism research by empirically analysing separately both tangible and intangible elements and their association with repeat visitation that is mediated by the tourist satisfaction. Therefore, a more holistic approach relating the antecedents of tourist repeat visit intention is proposed.